SPECIAL HELICES ON EQUIFORM DIFFERENTIAL GEOMETRY OF SPACELIKE CURVES IN MINKOWSKI SPACE-TIME - Bulut, Fatma; Bektas, Mehmet (Ankara Univ, Fac Sci, 2020)
In this paper, we establish k-type helices for equiform differential geometry of spacelike curves in 4-dimensional Minkowski space E-1(4). Also we obtain (k, m)-type slant helices for equiform differential geometry of spacelike curves in Minkowski space-time.
Keywords: Equiform Frenet Frame; k-type helices; (k, m)-type slant helices